Improving Students’ 21st Century Skills Through Creative Writing as A Creative Media - Helda Jolanda Pentury; Anastasia Dewi Anggraeni; Dendi Pratama (Deiksis, 2020)
The ability to improve students’ 21st century skills using creative writing is truly one of the most revolutionary developments in modern creative English education. This type of education, however, is not without its challenges, the way of using creative projects as the creative media to improve writing skills experiences showed the students and the teachers as well that to improve ‘21st century skills’ through creative writing is imaginative, and creative way. This study conducted an observation of design students at the University of Indraprasta PGRI Jakarta, especially their projects and literature study. The qualitative method with an integrated creative approach of 4C’s is used to analyze the creative writing elements of students’ creative projects as a creative media. The results of this study are useful to be used as a reference in improving students’ 21st century skills and creative writing skills as well by using those Creative Writing projects as a creative media. Furthermore, the results show most of the students have improved their 4C’s skills which is called 21st century skills, grow their language skills by writing the projects creatively and innovatively. Keywords: 21st century skill, creative writing, media